Human papillomavirus type 16 E7 oncoprotein causes a delay in repair of DNA damage - Park, Jung Wook; Nickel, Kwangok P.; Torres, Alexandra D.; Lee, Denis; Lambert, Paul F.; Kimple, Randall J. (Radiotherapy and oncology, 2014)
Patients with human papillomavirus related (HPV+) head and neck cancers (HNCs) demonstrate improved clinical outcomes compared to traditional HPV negative (HPV−) HNC patients. We have recently shown that HPV+ HNC cells are more sensitive to radiation than HPV− HNC cells. However, roles of HPV oncogenes in regulating the response of DNA damage repair remain unknown. Using immortalized normal oral epithelial cell lines, HPV+ HNC derived cell lines, and HPV16 E7-transgenic mice we assessed the repair of DNA damage using γ-H2AX foci, single and split dose clonogenic survival assays, and immunoblot. The ability of E7 to modulate expression of proteins associated with DNA repair pathways was assessed by immunoblot. HPV16 E7 increased retention of γ-H2AX nuclear foci and significantly decreased sublethal DNA damage repair. While phospho-ATM, phospho-ATR, Ku70, and Ku80 expressions were not altered by E7, Rad51 was induced by E7. Correspondingly, HPV+ HNC cell lines showed retention of Rad51 after γ-radiation. Our findings provide further understanding as to how HPV16 E7 manipulates cellular DNA damage responses that may underlie its oncogenic potential and influence the altered sensitivity to radiation seen in HPV+ HNC as compared to HPV− HNC.